If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(y + -8) = 7(4 + y) Reorder the terms: 8(-8 + y) = 7(4 + y) (-8 * 8 + y * 8) = 7(4 + y) (-64 + 8y) = 7(4 + y) -64 + 8y = (4 * 7 + y * 7) -64 + 8y = (28 + 7y) Solving -64 + 8y = 28 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -64 + 8y + -7y = 28 + 7y + -7y Combine like terms: 8y + -7y = 1y -64 + 1y = 28 + 7y + -7y Combine like terms: 7y + -7y = 0 -64 + 1y = 28 + 0 -64 + 1y = 28 Add '64' to each side of the equation. -64 + 64 + 1y = 28 + 64 Combine like terms: -64 + 64 = 0 0 + 1y = 28 + 64 1y = 28 + 64 Combine like terms: 28 + 64 = 92 1y = 92 Divide each side by '1'. y = 92 Simplifying y = 92
| V=37 | | 22x-6x-16=10x-20+6x | | M+0.26=6.2 | | 0.5(0)+3= | | 22x^2+18x-100= | | 5x^4-2x^3+20x^2-8x=0 | | 5(x-7)=(-45) | | 10-x/90-x | | 0.5(-4)+3= | | x^4-18x^2-40=0 | | 0.5(-2)+3= | | 14c=9c-10 | | -13+(-12)= | | -3(-8x+9)-2x=6(x-6)-9 | | 5x^2-9=6 | | (x+jy)-(x-jy)+2-4j=2j(x+jy) | | (x+2)+x=22 | | -13x-26=20/13 | | 4x+-3x=2 | | 6(x+2)+4(3x-1)=30 | | 9+2*5x=12 | | (x+iy)-(x-iy)+2-4i=2i(x+iy) | | (-110)(0.5)= | | .3(x+6)=.5(x-2) | | -4+2y=2y+6+y | | X^2+6x=357 | | 2*b=10 | | -5/2w=-25 | | 3w-9+3(3w+1)=-2(w+2) | | 20x-14x=34 | | -4/5u=-28 | | 8x^5+27x^2=0 |